The parsec–scale relationship between ICO and AV in local molecular clouds. Issue 4 (30th October 2017) - Lee, Cheoljong; Leroy, Adam K; Bolatto, Alberto D; Glover, Simon C O; Indebetouw, Remy; Sandstrom, Karin; Schruba, Andreas
Abstract: We measure the parsec–scale relationship between integrated CO intensity ( I CO ) and visual extinction ( A V ) in 24 local molecular clouds using maps of CO emission and dust optical depth from Planck . This relationship informs our understanding of CO emission across environments, but clean Milky Way measurements remain scarce. We find uniform I CO for a given A V, with the results bracketed by previous studies of the Pipe and Perseus clouds. Our measured I CO − A V relation broadly agrees with the standard Galactic CO-to-H2 conversion factor, the relation found for the Magellanic clouds at coarser resolution, and numerical simulations by Glover & Clark (2016 ). This supports the idea that CO emission primarily depends on shielding, which protects molecules from dissociating radiation. Evidence for CO saturation at high A V and a threshold for CO emission at low A V varies remains uncertain due to insufficient resolution and ambiguities in background subtraction. Resolution of order 0.1 pc may be required to measure these features. We use this I CO − A V relation to predict how the CO-to-H2 conversion factor ( X CO ) would change if the Solar Neighbourhood clouds had different dust-to-gas ratio (metallicity). The calculations highlight the need for improved observations of the CO emission threshold and H i shielding layer depth. They are also sensitive to the shape of the column density distribution. Because local clouds collectively show a self-similar distribution, we predict a shallow metallicity dependence for X CO down to a few tenths of solar metallicity. However, our calculations also imply dramatic variations in cloud-to-cloud X CO at subsolar metallicity.